2016
DOI: 10.1016/j.ijsu.2015.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer invading the airway: diagnosis and management

Abstract: Although some patients are currently referred with a severely advanced disease, the indication for tracheotomy, salvage procedures or supportive care has decreased over time. Resection is feasible for differentiated tumors with an overall good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 10 publications
0
26
0
1
Order By: Relevance
“…Our data might be affected by the limited number of examined cases but, also based on previous experience [6], TIR3B is anyway a lesion with a significant high risk for cancer. When cancer is present, although not associated to severe prognosis since it usually shows a general benign course especially for small nodules, it remains a cancer with potential aggressiveness [26]. Emphasis must be placed on the appropriateness of care and avoidance of over-and under-treatment and mainly on avoidance of reoperation for completion thyroidectomy which is usually required, as in our series, when a TIR3B nodule is revealed as malignant at histopatology according to the international guidelines [27].…”
Section: Discussionmentioning
confidence: 85%
“…Our data might be affected by the limited number of examined cases but, also based on previous experience [6], TIR3B is anyway a lesion with a significant high risk for cancer. When cancer is present, although not associated to severe prognosis since it usually shows a general benign course especially for small nodules, it remains a cancer with potential aggressiveness [26]. Emphasis must be placed on the appropriateness of care and avoidance of over-and under-treatment and mainly on avoidance of reoperation for completion thyroidectomy which is usually required, as in our series, when a TIR3B nodule is revealed as malignant at histopatology according to the international guidelines [27].…”
Section: Discussionmentioning
confidence: 85%
“…Tracheotomy during thyroid surgery is rare due to tracheal invasion or bilateral recurrent laryngeal nerve injury. Avenia et al ( 22 ) reported that only 43 (1.9%) of 2,165 thyroid cancer patients required tracheotomy. Similar findings were also noted in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies thus may not have taken advantage of the calcifying properties of the periosteum. 2,3,10,11 If the surgery has not included a proper mobilization of the periosteum, then this may result in a soft muscular flap leading to dynamic collapse in the tracheal window. The blood supply of the SCM flap has been described by Kierner et al 12 If the circulation is compromised due to an inadequate amount of vascularized muscle attached to the periosteal flap, then this may also lead to unsatisfactory results in terms of establishing a stable airway.…”
Section: Surgical Notesmentioning
confidence: 99%